1995
DOI: 10.2166/wst.1995.0044
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous removal of organic materials and nitrogen by micro-aerobic biofilms

Abstract: Simultaneous nitrification with denitrification was investigated using a single rotating biological contactor (RBC). The authors proposed two means to achieve simultaneous nitrification with denitrification in the single reactor: (1) to control oxygen transfer rate by reducing oxygen partial pressure (P02) in the air phase and (2) to develop a combined partially (aerobic) and fully (anaerobic) submerged RBC (CPFSR) reactor. For the former experiment, the maximum denitrification efficiency of 90 % was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…This evidence supported the previous observations that slow-growing nitrifiers and even strict anaerobes (SRB) were abundantly present in the surface of the actively growing heterotrophic biofilms (Okabe et al, 1996a,b;Watanabe et al, 1995). The nitrifiers could grow even at a low rate and make up for the loss of their population by detachment and displacement in the biofilm.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This evidence supported the previous observations that slow-growing nitrifiers and even strict anaerobes (SRB) were abundantly present in the surface of the actively growing heterotrophic biofilms (Okabe et al, 1996a,b;Watanabe et al, 1995). The nitrifiers could grow even at a low rate and make up for the loss of their population by detachment and displacement in the biofilm.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies, however, have shown that a large amount of slow growing bacteria (e.g., nitrifiers) were abundantly present in actively growing heterotrophic biofilms (Okabe et al, 1996a,b;. Furthermore, sulfate reducing bacteria (strict anaerobes) were also present in the surface of an actively growing aerobic mixed population biofilm (Watanabe et al, 1995). These experimental evidences cannot be explained by the existing biofilm accumulation models.…”
Section: Introductionmentioning
confidence: 90%
“…The biofilm can also provide a long retention time for bacteria and yield less sludge. Some researchers have studied conventional biological nitrogen removal and enhanced biological phosphate removal (EBPR) in SBBR [16][17][18]. Also a few researchers have investigated SND in SBBR, mainly in DO, pH and carbon source [7,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The reactor feeding consisted of synthetic wastewater with characteristics similar to those of domestic wastewater (Watnabe et al, 1995). It was prepared by using tap water, dechlorinated by the use of sodium thiosulfate, and the addition of dosages of chemicals, as indicated in Table 1.…”
Section: Experimental Operating Proceduresmentioning
confidence: 99%